Media suicide-reports, Internet use and the occurrence of suicides between 1987 and 2005 in Japan - Abe Takeru; Tarumi Kimio; Hagihara Akihito (BMC, 2007)
Abstract Background Previous investigations regarding the effects of suicide reports in the media on suicide incidence in Japan have been limited and inconclusive and, although Internet use has greatly increased, its influence on suicide is completely unknown. Thus, the relationship between newspaper articles about suicide, Internet use, and the incidence of suicide in Japan was examined. Methods A linear model was fitted to time series data from January 1987 to March 2005 (218 months). Results Consistent with previous findings, the number of newspaper articles about suicide was a predictor of suicide among both male and female subjects. Internet use was also a predictor of suicide among males, probably because males spent more time online than females. Conclusion Because this is the first, preliminary study examining the association between Internet use and suicide, further research is required to verify the present findings.